Kompetensi Pengetahuan Pedagogi Konten melalui Workshop pada Peserta PPG SM3T Pendidikan Biologi-UR - Yustina Yustina; Wansyafii Wansyafii (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
This descriptive study was conducted from April 2015 to September 2016 which was aimed at investigating the competency profiles of PPG SM3T participants using workshop. It applied total sampling technique which involve 17 teacher candidates of PPG SM3T-UR. The parameters in this study were the competence which covers 8 aspect: pedagogical knowledge PK (Lesson plan, Student worksheet, Teaching materials, Instrument assessment); Conten knowledge CK (formatif test, local test and national test) and pedagogical content knowledge PCK (peerteaching). The data were gathered by means of observation sheet, porthpolio, and test. The data analysis was conducted by determining the mean scores, percentage which were tabulated, histogram and then descriptively analyzed.The findings demonstrated that the participants’ competence were categorized pedagogical content knowledge (PCK)  into very good level attained the mean scores peerteaching  (88.59), and pedagogical knowledge (PK) the mean scores (81- 85) which were categorized into good level. Content knowledge (CK) the mean scores formatif test, local tes and national test were 78,94; 78,44; 71, 86 which were categorized tendency to be into good level. aspect PK and CK that owned tendency determine for PCK. Whereas, the only aspect (PK) which had formatif test tendency to decline in the cycle-1. The other five cycle had tendency to increase. This study concluded that  the workshop was fully evident to develop the good PK, CK were contribution for PCK of the PPG SM3T-UR’s participant